Evaluation of post-operative outcome in different surgical management for benign adnexal mass in children (Journal of Paediatric Surgeons of Bangladesh, 2019)
Background: An adnexal mass in pediatric age group is a rare entity. The differential diagnosis includes ovarian lesions, tubal or paratubal lesions, non-gynecologic lesions, and lesions related to infection or pregnancy. Presenting symptoms vary and may include acute abdominal pain, mass effect, and less commonly, precocious puberty and vaginal bleeding. Most of these lesions represent benign pathology, but malignant lesions are also a possibility, and appropriate surgical and postoperative management is essential. It is important for clinicians caring for these patients to understand the differential diagnosis of an adnexal mass, to facilitate correct management (whether surgical or nonsurgical) and necessary referrals where appropriate. Timely management can lessen initial morbidity & preserve fertility in future.Objective: The overall objective of this study is to evaluate post-operative outcome in different surgical management for benign adnexal mass in children.Materials and Methods: We are conducting a prospective observational study with the intention to observe the postoperative periods of 30 purposively selected patients having surgical management for adnexal mass in multiple centres in Dhaka city, over a period of 24 months from January, 2017 to December, 2018. Children upto 14 years of age with benign adnexal mass are planned to be selected as study subjects. After detailed history taking and thorough physical examination, all children are subjected to investigate for Blood for TC, DC, Hb%, CXR PA view, Urine R/M/E, Serum creatinine, USG of whole abdomen with pelvis special attention towards uterus and adnexae, áFP, âHCG, LDH, CA-125, CT scan of whole abdomen preoperatively. Information on post operative complications eg, post operative pain by age appropriate pain scale 0, 3rd and 8th POD, vomiting, wound infection, wound dehiscence and wound C/S report (if infection occurs) documented. Length of hospital stay is noted. Biopsy report of excised adnexal mass is reviewed. Informed written consent from parents or legal guardian is taken after describing the study objectives. Ethical clearance has been sought from the Ethical Committee of Dhaka Medical College and CMH, Dhaka.Results: Total 15 patients are studied till now. From this limited data we have observed that there has been apparently minimum difference among different surgical management for benign adnexal mass regarding postoperative outcome.Conclusion: This is an on-going study. Specific conclusion could not be drawn at this early stage.Journal of Paediatric Surgeons of Bangladesh (2017) Vol. 8 (2): 52-57